Strong Ground Motion Characteristics During Significant Earthquakes at BMKG Accelerograph Stations: JGPI and JBPI - Budi, Achmad Prasetia; Jambari, Jambari; Pamuji, Danang (Jurnal Meteorologi dan Geofisika, 2025)
Jayapura City is characterized by high seismicity, dense population, and rapid urban development, making it particularly vulnerable to earthquake hazards. This study analyzes strong ground motion characteristics, including peak ground acceleration (PGA), effective duration, and response spectral acceleration, using data from four significant earthquakes that occurred between 2021 and 2022. PGA values were determined by identifying the peak of the acceleration spectrum, while response spectral acceleration was obtained and plotted as a function of period versus amplitude. Effective duration was evaluated using the concept of significant duration based on the 5–95% Arias intensity interval. Ground motion data were recorded by accelerograph stations operated by the Meteorological, Climatological, and Geophysical Agency (BMKG), specifically the JGPI and JBPI stations. The results show that PGA values at JGPI Station are consistently higher than those at JBPI Station, which is attributed to the hard soil conditions at JGPI. Hard soil tends to resonate at higher frequencies and exhibits greater damping, resulting in shorter effective durations. In contrast, JBPI Station, characterized by relatively softer soil conditions, exhibits longer effective durations. Furthermore, the response spectral acceleration values recorded at both stations for all analyzed earthquakes are lower than the design response spectra specified in SNI 1726:2019, indicating that although the earthquakes were felt, they did not cause significant structural damage, consistent with observed field conditions.